DAMPAK DANA ALOKASI UMUM, DANA ALOKASI KHUSUS, DAN DANA BAGI HASIL TERHADAP KETIMPANGAN PRODUK DOMESTIK REGIONAL BRUTO DI PROVINSI SULAWESI SELATAN PERIODE 2005 – 2014 - Muhammad Azizi (Delilah Tinggi Ilmu Ekonomi Jambatan Bulan, 2018)
The aims of this research are: (1) to find out the effect of special allocation fund component on the decrease in gross regional domestic product (GRDP) disparity between districts of South Celebes province period 2005-2014, (2) to know the effect of general allocation fund component on the decrease of gross regional domestic product inequality (GRDP) between districts in south Celebes province period 2005-2014, (3) to know the effect of profit sharing component on the decreasing inequality of gross regional domestic product inequality (GRDP) between districts in South Celebes province period 2005-2014. Data collection method using documentation method. The data collected were obtained from the central statistical agency of South Celebes province. To analyze the data used multiple linear regression analysis method which is a quantitative method to analyze the data. more than one research variable. The result showed that: (1) the effect of general allocation funds on gross regional domestic product inequality in south celebes show the positive and significant results when the general allocation fund increased, the level of inquality of gross regional domestic product in celebes province will also increase, (2) the effect of special allocation funds on gross regional domestic product inequality in south celebes province show negative and significant result, where when the value of special allocation fund increases, the level of inequality of gross regional domestic product in South celebes province will decrease or vice versa if the value of special allocation fund decreased then the level of inequality of gross regional domestic product in South celebes province will increase,(3) the effect of profit sharing on the gross regional domestic product inequality shows negative and significant result where when the value of profit sharing proceeds the level of inequality of gross regional domestic product will decrease on the contrary if the value of profit-sharing fund decreased then the level of inequality of gross regional domestic product in will increase.